Analysis of corporate governance disclosure, environmental performance and company value (study on manufacture companies in indonesia stock exchange for 2015-2019) (Lighthouse Publishing, 2022)
Companies must try to find new ways to improve their products in the era of the industrial age 4.0. This is because the competition in industry 4.0 is getting more challenging, so management will try to keep the company's revenue growth. This study uses institutional ownership, the proportion of independent commissioners, the size of the audit committee, and environmental performance as independent variables and firm value as the dependent variable. The research method uses a quantitative approach with a research period of 2015-2019. The results show that the hypotheses for institutional ownership and the size of the audit committee are supported or accepted, while the hypotheses for the size of the audit committee and environmental performance are rejected. Obtaining the results of this study is expected to be the basis for evaluating and determining company policies. In addition, information regarding the research results provides a new perspective to the company that environmental performance is essential in maintaining the sustainability of living things and the company's operations around the community. In this study there are also limitations where the research period is limited to five years so that the results of hypothesis testing can only obtain two supported hypotheses. If the vulnerable research period is extended, the results of the hypothesis will provide more than two supported hypotheses. For further research, the authors provide suggestions in order to expand the research period in order to obtain wider research data and will provide good results compared to previous research.